Profil Protein Klebsiella pneumoniae K3 Pasca Inaktivasi Sinar Gamma dan Pemanasan Suhu 65 C - I. SUGORO; I. DJAJANEGARA (Fakultas Farmasi Universitas Pancasila, 2011)
Klebsiella pneumoniae is one of coliform bacteria which causes human and mammalian diseases. The bacteria dominate in dairy cow milk which has been infected by mastitis and has resistent on antibiotic. Vaccination is one of aims to prevent the diseases. Nuclear technique could be used to have a vaccine candidate.This research was conducted to get inactivated K. pneumoniae by gamma irradiation and heat inactivated as vaccine candidate. The experiments were done by determination of inactivated doses, protein content, and protein profile. analysis. K. pneumoniae could be inactivated using gamma rays by doses higher than 600 Gy. Neither irradiation nor heat (65 oC) influenced the K. pneumoniae total protein content The intensity of protein profile in gamma ray inactivated was higher than heat inactivated. There were 35, 36, and 60 kDa protein which were diagnosed as antigen protein. It could be concluded that inactivated by gamma irradiation K. pneumoniae could be chosen as a vaccine candidate and as a model for other bacterial vaccine.